Perancangan Website Sekolah SLB N Salatiga Dengan Wordpress - Mahendra, Fajar, Dr. Heru Supriyono, M.Sc (2016)
SLBN (special education school) of Salatiga which was founded in 1983 it has been organizing educational services TKLB level, SDLB, SMPLB, and SMALB. Along with the increasing number of students SLBN of Salatiga require the media information that facilitate the public to get information. Information about SLBN of Salatiga previously only available through leaflets or by going directly to the school. The main problem facing society SLBN of Salatiga is difficult to obtain information about the SLBN Salatiga. Of these problems the authors create a website for SLBN of Salatiga, so the public is more easy in search of information. Designing the website SLBN of Salatiga are use wordpress as a medium in the design. Making a website focused on providing information relating to the SLBN of Salatiga. This website consists of pages that contains the profile of the school, such as history, vision, and mission. Then update school facilities, student affairs and news about the SLBN of Salatiga. Website testing is done with a deep interview to teachers and the general public. The author conducted interviews with teachers of the school as the website administrator. The existence of this website according to the teachers are very helpful in disseminating information and availability of media delivery that is easily accessed by everyone. Besides that, the interview was also conducted with the public, they feel helped by SLBN of Salatiga website. So the information needed about SLBN of Salatiga they can get easily. With this website, the school can provide the information that needed by public about the educational SLBN of Salatiga.